Optimized-Eight-State CV-QKD Protocol Outperforming Gaussian Modulation Based Protocols - Ivan B. Djordjevic (IEEE Photonics Journal)
In this paper, an optimized-eight-state CV-QKD protocol is proposed significantly outperforming previously introduced discrete modulation (DM) protocols as well as the corresponding Gaussian modulation (GM)-based CV-QKD protocols for practical reconciliation efficiencies values in terms of both secret-key rate (SKR) and achievable distance. The proposed CV-QKD protocol also outperforms, in terms of SKR, the corresponding high-cost single-photon DV-QKD scheme, employing an array of multiplexed single-photon detectors, for several orders of magnitude. We also describe a generalized RF-assisted CV-QKD scheme with heterodyne detection applicable to arbitrary DM scheme, insensitive to the laser phase noise and frequency offset fluctuations.